Effects of music intervention on sleep quality of older adults: A systematic review and meta-analysis - Cong Wang; Guichen Li; Lufang Zheng; Xiangfei Meng; Qiuyan Meng; Shuo Wang; Huiru Yin; Jianfeng Chu; Li Chen (Elsevier, 2021)
Background: Music interventions have several benefits for sleep quality. However, the effects of music interventions on sleep quality in older adults are controversial. Objective: To summarize and evaluate the efficacy of music interventions on sleep quality in older adults. Methods: The Cochrane Library, Embase, PubMed, Web of Science and Chinese National Knowledge Infrastructure (CNKI) were systematically retrieved until June 2020, updated on March 13, 2021. Both experimental and quasi-experimental studies were included if they evaluated the efficacy of music interventions on sleep outcomes in older adults. The methodological quality was assessed by the Cochrane RoB 2.0 and ROBINS-I Tool. The random effects models and effect measure (MD) were adopted, and sensitivity analysis by omitting each study was conducted to explore the source of heterogeneity. Results: A total of 489 participants from 9 studies met the inclusion criteria. 6 studies were included in meta-analysis and sensitivity analysis, and 3 studies were included in the qualitative analysis. Main concerns about risk of bias were lack of blinding participants and investigators, and confounding factors might exist in non-RCTs. The Post-hoc meta-analysis indicated that music interventions might have a positive effect on sleep quality [MD = −2.64, 95 % CI (−3.76, −1.53), p <  0.001; I2 = 75.0 %]. Only one study evaluated adverse events and reported zero discomfort. Conclusions: The results indicated that music interventions might be beneficial for improving sleep quality, especially in sleep latency, sleep duration, sleep efficiency and sleep of daytime dysfunction in elderly individuals.